2021
DOI: 10.1007/s00726-021-02980-2
|View full text |Cite
|
Sign up to set email alerts
|

Taurine suppresses liquid–liquid phase separation of lysozyme protein

Abstract: Taurine is a compatible osmolyte that infers stability to proteins. Recent studies have revealed that liquid-liquid phase separation (LLPS) of proteins underlie the formation of membraneless organelles in cells. In the present study, we evaluated the role of taurine on LLPS of hen egg lysozyme. We demonstrated that taurine decreases the turbidity of the polyethylene glycol-induced crowding solution of lysozyme. We also demonstrated that taurine attenuates LLPS-dependent cloudiness of lysozyme solution with 0.5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Although previous research on Lys–Alb droplets using fluorescence microscopy has revealed the presence of Lys inside the liquid droplets, 52 to the best of our knowledge, the presence of Alb in these droplets has not previously been demonstrated experimentally. Thus, we conducted Raman analysis with 50 mg ml −1 Lys and 50 mg ml −1 Alb solutions without the crowding agent ( i.e.…”
Section: Resultsmentioning
confidence: 65%
“…Although previous research on Lys–Alb droplets using fluorescence microscopy has revealed the presence of Lys inside the liquid droplets, 52 to the best of our knowledge, the presence of Alb in these droplets has not previously been demonstrated experimentally. Thus, we conducted Raman analysis with 50 mg ml −1 Lys and 50 mg ml −1 Alb solutions without the crowding agent ( i.e.…”
Section: Resultsmentioning
confidence: 65%
“…These assumed benefits determined an increase in the global taurine market size, which was USD 264 million in 2020 and is expected to reach USD 434 million in 2021 [68]. Nevertheless, contrary to other osmolytes present in cells like trimethylamine N-oxide [17,[69][70][71][72], taurine had not been widely investigated in its molecular interactions with biomolecules, neither in its modification of water network until now, with the exception of a few recent works [37,59,73], at our knowledge. Thus, to fill the gap concerning this osmolyte represents an important challenge, above all for its relevance in several medical issues and its increasing consumption.…”
Section: Discussionmentioning
confidence: 99%
“…This interesting study revealed that sucrose enhances the stability of LLPS, whereas BSA hinders it . Tsubotani et al (2021) showed that taurine inhibits LLPS of lysozyme by decreasing its turbidity and cloudiness across different circumstances . Taratuta et al (1990) investigated the influence of pH and the specific type of salt, emphasizing the significance of ionic conditions in LLPS .…”
mentioning
confidence: 99%
“…5 Tsubotani et al (2021) showed that taurine inhibits LLPS of lysozyme by decreasing its turbidity and cloudiness across different circumstances. 6 Taratuta et al (1990) investigated the influence of pH and the specific type of salt, emphasizing the significance of ionic conditions in LLPS. 7 The hypothesis of lysozyme amyloid formation has evolved significantly over time.…”
mentioning
confidence: 99%